A review of the biology of the genus Isognomon (Bivalvia; Pteriidae) with a discussion on shellfish reef restoration potential of Isognomon ephippium. (1st October 2020) - Benthotage, Chamara; Cole, Victoria J.; Schulz, Kai G.; Benkendorff, Kirsten
ABSTRACT: This review investigates the current state of knowledge of the genus Isognomon with respect to different aspects of its biology, including taxonomy, morphology, ecology, life history, physiology, stress tolerance, diseases, contamination from environmental pollutants and their potential for use as bio-indicators. A total of 126 publications on the monophyletic genus Isognomon were identified in structured searches, with 30 reports on Isognomon ephippium, a reef-forming leaf oyster of potential interest for use in shellfish reef restoration programmes. Isognomon ephippium is the largest species in the genus, and occurs in an array of subtropical and tropical estuarine habitats such as mangroves, mudflats, sandy bottoms and rocks, where it can increase the architectural and biological diversity of the ecosystems. Isognomon spp. appear to have a low incidence of disease and have been used as bio-indicators in a range of environmental and contamination studies. For future use in shellfish restoration programmes, further information is required on the life history of I. ephippium, including age at sexual maturity, spawning times, fecundity and larval development, to facilitate spat production and supply. Further characterisation of the physiology and immune system of I . ephippium would facilitate future monitoring of the health of natural and restored populations.